PENGARUH STORE ATMOSHPERE, SERVICE QUALITY DAN PRODUC DIVERSITY TERHADAP MINAT BELI KONSUMEN (Pada KFC Metropolitan City Pekanbaru) - Putriand, Deby Dinanda; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This researcher aims to find out how much influence store atmosphere, service quality and produc diversity have on consumer buying interest in KFC metropolitan City Pekanbaru. The sample in this study was taken as many as 100 respondents and the technique used was Accidental Sampling. The data in this study uses a survey method through a questionnaire filled out by consumers. Data obtained from the questionnaire and then processed to then be tested with statistics through SPSS. The results of the analysis use simple linear regression analysis, multiple linear regression analysis, determination test (R2), individual significant test (t test), and simultaneous significant test (F test) so that it can be known that store atmosphere variables influence consumer purchase interest variables, variables , service quality influences the variables of consumer buying interest, and variable productivity diversity influences consumer buying interest and store atmosphere variables, service quality and diversity products influence simultaneously on the variables of consumer buying interest. The calculation results show that R square is the coefficient of determination and the value of R Square is 0.847. This means that store atmosphere, service quality and produc diversity affect consumer buying interest by 84.7%.Â Â Keywords: Store Atmosphere, Service Quality and Diversity Products and Consumer Buying Interests